2021
DOI: 10.1021/acs.joc.1c01048
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Succinimide Spiro-Fused Sultams from the Reaction of N-(Phenylsulfonyl)acetamides with Maleimides via C(sp2)–H Activation

Abstract: Presented herein is an effective preparation of succinimide spiro-fused sultams through the coupling reaction of N-(phenylsulfonyl)acetamides with maleimides. It is deduced that this reaction should proceed through a cascade process including Rh(III)-catalyzed C(sp 2 )−H bond cleavage of N-(phenylsulfonyl)acetamide, maleimide double bond insertion into the C−Rh bond, β-hydride elimination, reductive elimination, and intramolecular aza-Michael addition. Notably, this cascade procedure features simultaneous annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…30 Moreover, the NH unit in N-( phenylsulfonyl)acetamides was viable in assisting the CHA reaction with maleimides to give succinimide spiropyrazolo[1,2-a]pyrazolones (Scheme 37). 31 The formation of the product involves the generation of a five-membered rhodacycle via C-H activation, coordination with maleimide, migratory insertion, isomerization, β-hydride elimination, reductive elimination and aza-Michael addition (Scheme 37).…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…30 Moreover, the NH unit in N-( phenylsulfonyl)acetamides was viable in assisting the CHA reaction with maleimides to give succinimide spiropyrazolo[1,2-a]pyrazolones (Scheme 37). 31 The formation of the product involves the generation of a five-membered rhodacycle via C-H activation, coordination with maleimide, migratory insertion, isomerization, β-hydride elimination, reductive elimination and aza-Michael addition (Scheme 37).…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…Recently, in 2021, Hu et al reported the Rh-catalyzed spirosultams 76 from the reaction of phenylsulfonylacetamides 75 and maleimide 16 derivatives in the presence of NaOAc in ethylacetate medium at 120 °C (Scheme 15). 19 During the optimization study, several additives such as KOAc, CsOAc, AgOAc, Cs 2 CO 3 , K 3 PO 4 , AcOH and PivOH were screened to find out the best combination of the additives and catalyst. It was observed that NaOAc was the best additive to give a high yield of the products.…”
Section: Secondary Amide/sulfonamide Directed Spirocyclizationmentioning
confidence: 99%
“…[183i] Fortunately, these barriers were overcame by an elegant transition-metal-catalyzed directing group assisted functionalization of CÀ H bond followed by intramolecular annulation or spirolization using easily accessible starting materials. [183j,k] Expanding the above stratergies Hu and co-workers further realized a novel and efficient synthesis of succinimide spirofused sultams through Rh(III)-catalyzed C(sp 2 )-H bond functionalization followed by [4 + 1] [184]…”
Section: Rhodium Catalyzed C-h Activationmentioning
confidence: 99%
“…Finally, intramolecular aza‐Michael reaction of intermediate IV afforded the product 303 (Scheme 89). [184] …”
Section: Introductionmentioning
confidence: 99%